SAFFIOTI, Heleieth I. B. A mulher na sociedade de classes: mito e realidade. 3.ed. São Paulo: Expressão Popular, 2013. 528p. (REVHIST - Revista de História da UEG, 2021)
Resenha da Obra: SAFFIOTI, Heleieth I. B. A mulher na sociedade de classes: mito e realidade. 3.ed. São Paulo: Expressão Popular, 2013. 528p.